Overview of a media convergence centre (MC2) - Talevski, Alex; Chang, Elizabeth; Dillon, Tharam S. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Organizational alliances are rapidly being formed as a means for effective cooperation with a common goal within a targeted value chain. The combination of such communication, coordination and cooperation leads to new organisational forms and scenarios within the Digital Ecosystem space that require technological support. Convergence refers to the move towards the use of a single united interaction medium and media. Such a solution enables telecommunications services that are concurrently coupled with enterprise and internet data. Due to the versatile nature of today's extended enterprise, a flexible, feature-rich, adaptive and widely accessible converged solution is required.This paper proposes a Media Convergence Centre (MC:) solution that allows users to participate in a converged multimedia collaboration network using a variety of interaction devices in an easy and convenient manner.